2018
DOI: 10.1167/iovs.18-25186
|View full text |Cite
|
Sign up to set email alerts
|

Partial Rescue of Ocular Pigment Cells and Structure by Inducible Ectopic Expression of Mitf-M in MITF-Deficient Mice

Abstract: PurposeComplete deficiency of microphthalmia transcription factor (MITF) in Mitfmi-vga9/mi-vga9 mice is associated with microphthalmia, retinal dysplasia, and albinism. We investigated the ability of dopachrome tautomerase (DCT) promoter-mediated inducible ectopic expression of Mitf-M to rescue these phenotypic abnormalities.MethodsA new mouse line was created with doxycycline-inducible ectopic Mitf-M expression on an Mitf-deficient Mitfmi-vga9 background (DMV mouse). Adult DMV mice were phenotypically charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…This study reviewed the changes of Mitf-M mutation on gene expression in the cochlea. Mitf has many subtypes [38], in which type M is specifically expressed in melanocytes [39], by direct association with related pigmentases such as tyrosinase (Tyr), dopachrome tautomerase (Dct), endothelin receptor type B (Ednrb), and solute carrier family 45 member 2 (Slc45a2), regulating the survival, migration, and differentiation of melanocytes [40]. Among them, Mitf-M gene [38,39] plays a key role in regulating tyrosine metabolic pathway and melanin production, mainly regulating downstream pigment-related enzymes such as Tyr, Dct, and Tyrp1.…”
Section: Discussionmentioning
confidence: 99%
“…This study reviewed the changes of Mitf-M mutation on gene expression in the cochlea. Mitf has many subtypes [38], in which type M is specifically expressed in melanocytes [39], by direct association with related pigmentases such as tyrosinase (Tyr), dopachrome tautomerase (Dct), endothelin receptor type B (Ednrb), and solute carrier family 45 member 2 (Slc45a2), regulating the survival, migration, and differentiation of melanocytes [40]. Among them, Mitf-M gene [38,39] plays a key role in regulating tyrosine metabolic pathway and melanin production, mainly regulating downstream pigment-related enzymes such as Tyr, Dct, and Tyrp1.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have generated a specific Mitf‐M knockout mouse and demonstrated that the loss of MITF‐M results in the loss of iris stromal and choroidal melanocytes. Our findings also demonstrate that while Mitf‐M may be expressed in the adult RPE (Maruotti, Thein, Zack, & Esumi, ) and can rescue the loss of pigmentation in Mitf vga9 mice (Michael et al, ), it is not required for pigmentation of the RPE. Additionally, the loss of Mitf‐M increased the size of the kidneys (Figure ), indicating that the loss of a single isoform affects distinct tissues differently, further highlighting the utility of the isoform‐specific knockout reagents generated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…(b) examination of the expression pattern of isoforms in target tissues of wild-type and Mitf mutant animals to infer their function during development (Bharti et al, 2008); (c) isoform-specific overexpression studies to determine the function of individual isoforms (Michael et al, 2018); or (d) isoform-specific knockouts as previously performed (Bharti et al, 2012;Phelep et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation